Oil Intensities and Oil Prices : Evidence for Latin America - Alaimo, Veronica; Lopez, Humberto (World Bank, Washington, DC, 2012)
Crude oil prices have dramatically increased over the past years and are now at a historical maximum in nominal terms and very close to it in real terms. It is difficult to argue, at least for net oil importers, that higher oil prices have a positive impact on welfare. In fact, the negative relationship between oil prices and economic activity has been well documented in the literature. Yet, to the extent that higher oil prices lead to lower oil consumption, it would be possible to argue that not all the effects of a price increase are negative. Climate change concerns have been on the rise in recent years and fossil fuel consumption is generally viewed as one of the main causes behind it. Thus this paper explores whether higher oil prices contribute to lowering oil intensities (that is, oil consumption per unit of gross domestic product). The findings show that following an increase in oil prices, OECD countries tend to reduce oil intensity. However, the same result does not hold for Latin America (and more generally for middle-income countries) where oil intensities appear to be unaffected by oil prices. The paper also explores why this is so.